COMPOUNDING STRATEGIES IN TIV WORD FORMS - Nartondo, Janet Seember; Yina, Godwin; Adzer, Vanessa Chivir (EBSU Journal of Social Sciences and Humanities, 2024)
This research entitled ‘Compounding Strategies in Tiv Word Forms’ is concerned compounding strategies in Tiv word forms. It shows the various ways by which compounds are uniquely formed in Tiv. The study is based on the De Saussurean Theory of Structuralism; suggesting language as a system of systems; a structure that is made up of other structures or sub-units. The data was sourced primarily from a select number of written sermons in Tiv as well as the researcher’s competent knowledge of Tiv with some amount of information obtained from textbooks and other research works. The findings show that compound nouns in Tiv are created with combinations of: noun + noun; noun + verb; noun+ adjective; Noun+ preposition; adjective + noun; adjective + verb; verb + noun; verb + adjective; preposition + noun; compound pronouns exist in Tiv with determiners and nouns; possessives and nouns; and determiners and pronouns combinations; compound adjectives are consisted mostly of number adjectives; and compound adverbs dominantly come in the form of reduplicatives. It concludes that attention must be paid to the fact that Tiv has its own unique structure as regards availability, prominence and combinatory order of constituent elements of the selected compounds.